Insights into the Roles of B Cells in Patients with Sepsis - Xijie Dong; Hao Tu; Shuang Qin; Xiangjun Bai; Fan Yang; Zhanfei Li (Journal of Immunology Research)
Sepsis is a life-threatening yet common disease, still posing high mortality worldwide. Sepsis-related deaths primarily occur during immunosuppression; the disease can hamper the numbers and function of B cells, which mediate innate and adaptive immune responses to maintain immune homeostasis. Dysfunction of B cells, along with aggravated immunosuppression, are closely related to poor prognosis. However, B cells in patients with sepsis have garnered little attention. This article focuses on the significance of B-cell subsets, including regulatory B cells, in sepsis and how the counts and function of circulating B cells are affected in patients with sepsis. Finally, potential B-cell-related immunotherapies for sepsis are explored.